Russian Federation - Regional development and growth agglomerations : the longer term challenges of economic transition in the Russian Federation - World Bank (World Bank, 2012)
As Russia continues to make rapid general progress in building modem market institutions, the complex spatial dimension of transformation in the country will continue to present strong policy challenges for many years to come. In fact, these challenges are arguably becoming progressively stronger. As confirmed in this Country Economic Memorandum (CEM), economic growth has become much more unevenly distributed across the Russian Federation in recent years, with a sharp contrast opening up between growth agglomerations in much of the Western part of the country and much more modest development in the East and North. This CEM focuses on regional development in the Russian Federation. It first conducts an examination of recent trends in the regional dimension of growth based on available economic data for the country as a whole. Particular attention is given to the topics of convergence, agglomeration, and the sources of regional growth. In this endeavor, the analysis distinguishes between two quite different recent periods of economic growth: 1999-2003 and 2004-2006. A regional-level survey allows for the examination of perceptions of entrepreneurs working in two poorer-than-average regions that have been exhibiting impressive rates of growth in recent years: Rostov and Tver oblasts. The conclusions obtained in these investigations are then related to the question of what type of a national regional strategy, if any, might be useful for Russia.